Factors that Influence the Income of Salt Farmers in Kupang Regency, East Kupang District (Case Study of Merdeka Village) - Desriarisandi Natalia Gelu; Marthen R. Pelokila; Fransina W. Ballo (Formosa Journal of Applied Sciences, 2023)
The aim of this research is to find out how labor and capital influence the income of salt producers in Merdeka Village, East Kupang Regency. Multiple regression analysis, quantitative research methods, questionnaires, and documentation were used in this research to handle data depending on demand. The data processing technique used is multiple regression data analysis using SPSS 25, UI hypothesis testing, validity testing, and classical hypothesis testing. The findings of this study show that the capital variable increases salt farming income significantly and partially. The findings of this study show that the capital variable increases salt farming income significantly and partially.